A sensitive direct chiral liquid chromatography tandem mass spectrometry method for the enantio—Selective analysis of imeglimin in formulation - Sangamithra Ramalingam, Meyyanathan Nainar Subramania, Babu Basuvan, Ramesh Jaganathan, Anandha Jothi Dhavamani, Nagesh Kumar Kandukuri, Ratnam Venkata Parimi, Sandeep Bodduna (Journal of Applied Pharmaceutical Science, 2023)
The purpose of this study was to separate and develop a sensitive chiral liquid chromatography-tandem mass spectrometry (LC-MS/MS) technique to estimate the (+) and (−) enantiomers of imeglimin in its formulation and validate individual enantiomer of the drug. Imeglimin is used to treat type-2 diabetes (T2D). The chiral stationary phase was reverse phase Chiralpak IG-3 (100 × 4.6 mm, 3 μm), whereas the isocratic mobile phase was methanol and 10 mM ammonium acetate (95:5 v/v ratio) and the flow rate was 0.5 ml/minutes. The resolution of the (+) and (−) enantiomers was monitored using LC-ESI-MS/MS in positive transition at 155.0 m/z (M+H) for imeglimin. The (+) and (−) linearity ranges from 10 to 100 ng/ml. The correlation coefficient (R2) of the (+) and (−) imeglimin enantiomers was found to be linear. The retention time of the (+) and (−) enantiomers of the drug was 2.876 and 4.325 minutes and the total run time of the chromatographic resolution was 5 minutes. As a result, our goal is to separate the enantiomers and develop a fast, sensitive, and cost-effective method for estimating (+) and (−) enantiomers in its formulation.